Pengaruh Permainan Sorting Color Dalam Meningkatkan Kemampuan Klasifikasi Pra-Matematika Di Taman Kanak-Kanak Islam Budi Mulia - Juniati, Winda; Hazizah, Nur (Jurnal Golden Age, 2020)
The ability of children's mathematical classification is still low due to the lack of teacher's ability to create children's learning settings. So this study aims to improve the ability of pre-mathematical classification of early childhood. The method used in this research is literature study research. Which is motivated by an understanding of the importance of mathematical logic abilities related to child development. Data collection instruments use the collection of literature that is relevant to the object of discussion. The results of this study, indicate that the magnitude of the effect of color sorting games in improving the ability of pre-mathematical classification that can make children able to group objects according to color, shape, size and weight.